How Hospital Tours Affect Preoperative Anxiety in Mothers with Children Undergoing Open-Heart Surgery in Iran A Quasi-Experimental Study - Amintojari, Asal (International journal of community based nursing and midwifery, 2020)
Copyright: © International Journal of Community Based Nursing and Midwifery.